AVALIAÇÃO DA INFLUÊNCIA DO TIPO FACIAL NOS TAMANHOS DOS ESPAÇOS AÉREOS NASO E BUCOFARÍNGE - Castro, Aline Maria Alencar de (2006)
The variation in the sizes of the naso and oropharnyx space occurs due to genetic and/or enviromental factors. The reduction in the size of the nasopharnyx space, caused by the hipertrophy of the pharyngeal tonsil, have been associated to alterations in the facial growth pattern and to harmful effects in the occlusion. The objective of the present study is to evaluate if there is variation in the size of the naso and oropharnyx space in agreement with facial growth pattern, evaluate the agreement with the VERT index and a possible sexual dimorphism. In the measurement of the spaces, were used lateral roentgenography of 90 patients, divided in three groups according to facial craniofacial growth, determined by the VERT index. The patients of the sample, with ages between 9 and 16, had nasal respiratory mode, without any kind of nasal obstruction. It was not observed variation statistically significant in the size of naso and oropharnyx, when compared the three facial growth pattern. Besides, it was not found correlation between the size of the spaces and the VERT index and a sexual dimorphism was not observed.